Preparation of Palm Oil Industry’s Biomass-Based Graphene Composite for the Adsorptive Removal of Methylene Blue - Yeit Haan Teow (Hindawi - SAGE Publishing, 2021)
The ability of POME-based graphene shell composite (P-GSC), an adsorbent generated from oil palm wastes abundantly available in Malaysia such as POME and PKS, was examined in removing methylene blue (MB) dye by adsorption. Adsorption experiments, involving a batch column study and a batch equilibrium study, were conducted to investigate the efficiency of synthesized P-GSC from PKS as a base material in the removal of MB dye. The batch column study demonstrated that small-sized synthesized P-GSC from PKS as a base material could remove up to 98.5% for concentration. Therefore, the following batch equilibrium study was carried out on small-sized P-GSC only. Adsorption isotherms and kinetic isotherms were studied, from which the experimental data showed that the adsorption exhibited a good fit with the Freundlich model (R2=0.8923) and followed the pseudo-second order model (R2>0.98). FESEM, XPS, and XRD morphological and elemental analysis indicated the successful graphinization of POME on the P-GSC surface. The concept of deploying POME as the carbonaceous source to produce P-GSC, and then, deploying the resultant P-GSC as the adsorbent for MB dye removal has presented promising practical potential. Such cost-effective and environmentally friendly reuse of waste materials is envisioned to promote a ‘zero-waste industry.’